TANGGUNG JAWAB PERUSAHAAN DALAM PEMENUHAN JAMINAN SOSIAL KETENAGAKERJAAN DI KOTA TARAKAN - Darwis Manurung; Mawardi Khairi; Inggit Akim (Universitas Borneo Tarakan, 2021)
ABSTRACT Social security constitutes As a part of constitutional right for every citizen as mentioned in article 28 letter h paragraph 3 of the 1945 Constitution which states that everyone is entitled to social security which enables to development dignified human being. In addition, the provisions of Article 34 paragraph 2 of the 1945 Constitution also states that the state develops social security system for all people and empower the weak and incapable in accordance with human dignity. The fulfillment of labor rights by the company is a mandate of Law Number 13 Year 2003 on Manpower Article 86 paragraph 1 which states that every worker / laborer has the right to obtain protection for safety, health, morals, morals and treatment in accordance with the dignity and human dignity and religious values.Company policy in fulfilling labor rights on social security of labor is done through Collective Labor Agreement (PKB). In order to ensure the fulfillment of the right to social security of employment the Government of Tarakan City has issued Tarakan Mayor Instruction Number 2 Year 2014 on the Implementation of BPJS Employment Program through Licensing Administration in Tarakan City requiring employers / apprentices applying, extending permits to self-preservation and employee in BPJS Employment before the issuance of company licensing documents. The legal consequences for non-self-employed companies and their employees in the Employment BPJS program are subject to administrative sanctions to the imposition of criminal sanctions. While the legal consequences for the workforce are not able to claim compensation to BPJS Employment if experiencing work accident, death, pension and old age pension. Keyword: Rights of Worker, Company, Employment BPJS